(untitled)
Let I_α,b be the multilinear commutators of the fractional integrals I_α with the symbol b=(b_1, …,b_k ). We show that the constant of borderline weighted estimates for I_α is 1ε , and for I_α,b is 1ε^k+1 with each b_i belongs to the Orlicz space Osc_L^s_i . , number=3, journal=Analysis in Theory and Applications, year=2022, month=Sept., pages=404–425